Activation of Alpha-7 Nicotinic Acetylcholine Receptor Reduces Brain Edema in Mice with Ischemic Stroke and Bone Fracture - Dingquan Zou; Man Luo; Zhenying Han; Lei Zhan; Wan Zhu; Shuai Kang; Chen Bao; Zhao Li; Jeffrey Nelson; Rui Zhang; Hua Su (Molecular Neurobiology, 2017)

Growth Differentiation Factor 15 Is a Novel Diagnostic Biomarker of Mitochondrial Diseases - Xinbo Ji; Lizhen Zhao; Kunqian Ji; Yuying Zhao; Wei Li; Rui Zhang; Ying Hou; Jianqiang Lu; Chuanzhu Yan (Molecular Neurobiology, 2017)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

The use of toluidine blue staining combined with paraffin sectioning and the optimization of freeze-thaw counting methods for analysing root-knot nematodes in tomato - Xiaoman Li; Wenchao Zhao; Xiaoxuan Zhou; Jiaping Feng; Yingjian Gao; Xuehui Yao; Yang Liu; Jie Liu; Rui Yang; Fukuan Zhao; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

The responses of two native plant species to soil petroleum contamination in the Yellow River Delta, China - Wenjun Xie; Yanpeng Zhang; Rui Li; Hongjun Yang; Tao Wu; Liping Zhao; Zhaohua Lu (Environmental Science and Pollution Research, 2017)

Isolation and complete genome sequence of Halorientalis hydrocarbonoclasticus sp. nov., a hydrocarbon-degrading haloarchaeon - Dahe Zhao; Sumit Kumar; Jian Zhou; Rui Wang; Ming Li; Hua Xiang (Extremophiles, 2017)

Erratum to: Role of dopamine projections from ventral tegmental area to nucleus accumbens and medial prefrontal cortex in reinforcement behaviors assessed using optogenetic manipulation - Xiao Han; Man-yi Jing; Tai-yun Zhao; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2017)

Role of dopamine projections from ventral tegmental area to nucleus accumbens and medial prefrontal cortex in reinforcement behaviors assessed using optogenetic manipulation - Xiao Han; Man-yi Jing; Tai-yun Zhao; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

Synergistic roles of the E2 glycoprotein and 3′ untranslated region in the increased genomic stability of chimeric classical swine fever virus with attenuated phenotypes - Rui Wu; Ling Li; Lei Lei; Cheng Zhao; Xiaofang Shen; Haizhong Zhao; Zishu Pan (Archives of Virology, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Stability design charts for homogeneous slopes under typical conditions based on the double shear strength reduction technique - Gaopeng Tang; Lianheng Zhao; Li Liang; Shi Zuo; Rui Zhang (Arabian Journal of Geosciences, 2017)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Waterlogging risk assessment based on self-organizing map (SOM) artificial neural networks: a case study of an urban storm in Beijing - Wen-li Lai; Hong-rui Wang; Cheng Wang; Jie Zhang; Yong Zhao (Journal of Mountain Science, 2017)

Role of the SPS Gene Families in the Regulation of Sucrose Accumulation in Sugarcane - Dong-Liang Huang; Cui-Xian Qin; Yi-Yun Gui; Li-Han Zhao; Zhong-Liang Chen; Miao Wang; Yue Sun; Qing Liao; Yang-Rui Li; Prakash Lakshmanan (Sugar Tech, 2017)

Physiological characteristics and metabolomics of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene under high temperature stress - Xueli Qi; Weigang Xu; Jianzhou Zhang; Rui Guo; Mingzhong Zhao; Lin Hu; Huiwei Wang; Haibin Dong; Yan Li (Protoplasma, 2017)

Costimulation of soil glycosidase activity and soil respiration by nitrogen addition - Ji Chen; Yiqi Luo; Jianwei Li; Xuhui Zhou; Junji Cao; Rui‐Wu Wang; Yunqiang Wang; Shelby Shelton; Zhao Jin; Laura M. Walker; Zhaozhong Feng; Shuli Niu; et al. (Global Change Biology, 2017)
Unprecedented levels of nitrogen (N) have been deposited in ecosystems over the past century, which is expected to have cascading effects on microbially mediated soil respiration ( SR ). Extracellular enzymes play critical roles on the degradation of soil organic matter, and measurements of their activities are potentially useful indicators of SR . The links between soil extracellular enzymatic activities ( EEA s) and SR under N addition, however, have not been established. We therefore conducted a meta‐analysis from 62 publications to synthesize the responses of soil EEA s and SR to elevated N. Nitrogen addition significantly increased glycosidase activity ( GA ) by 13.0%, α ‐1,4‐glucosidase ( AG ) by 19.6%, β ‐1,4‐glucosidase ( BG ) by 11.1%, β ‐1,4‐xylosidase ( BX ) by 21.9% and β ‐D‐cellobiosidase ( CBH ) by 12.6%. Increases in GA were more evident for long duration, high rate, organic and mixed N addition (combination of organic and inorganic N addition), as well as for studies from farmland. The response ratios ( RR s) of GA were positively correlated with the SR ‐ RR s, even when evaluated individually for AG , BG , BX and CBH . This positive correlation between GA ‐ RR and SR ‐ RR was maintained for most types of vegetation and soil as well as for different methods of N addition. Our results provide the first evidence that GA is linked to SR under N addition over a range of ecosystems and highlight the need for further studies on the response of other soil EEA s to various global change factors and their implications for ecosystem functions.

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

The transgenic expression of human follistatin-344 increases skeletal muscle mass in pigs - Fei Chang; Rui Fang; Meng Wang; Xin Zhao; Wen Chang; Zaihu Zhang; Ning Li; Qingyong Meng (Transgenic Research, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Erratum to: Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)

Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)

Oxidized graphene-aggravated allergic asthma is antagonized by antioxidant vitamin E in Balb/c mice - Shuai Shang; Jinquan Li; Yun Zhao; Zhuge Xi; Zhisong Lu; Baizhan Li; Xu Yang; Rui Li (Environmental Science and Pollution Research, 2017)

Paenibacillus oryzisoli sp. nov., isolated from the rhizosphere of rice - Jun Zhang; Xiao-Tong Ma; Jun-Sheng Gao; Cai-Wen Zhang; Juan-Juan Zhao; Rui-Jie Zhang; Li-An Ma; Xiao-Xia Zhang (Antonie van Leeuwenhoek, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

cDNA library construction of two human Demodexspecies - DongLing Niu; RuiLing Wang; YaE Zhao; Rui Yang; Li Hu; YuYang Lei; WeiChao Dan (Acta Parasitologica, 2017)
The research of